Non-Tax State Revenue (PNBP) In Research Institute For Inland Fisheries And Extension (BRPPUPP) - Tike Dwi Putri (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2021)
This study aims to analyze Non-Tax State Revenue (PNBP) at Research Institute For Inland Fisheries And Extension (BRPPUPP) Tax in terms of recording accuracy, management compliance, and effectiveness. then analyzed using descriptive qualitative analysis method. The results of this study indicate that the percentage of PNBP for Research Institute For Inland Fisheries And Extension in 2019 the realization of PNBP receipts does not reach the target which shows that the performance of achieving the target is 89.5%, while the amount of revenue in 2020 illustrates the effectiveness of the PNBP policy exceeding the target of 198.9 %. Keywords: PNBP, BRPPUPP Abstrak Penelitian ini bertujuan untuk menganalisa Penerimaan Negara Bukan Pajak (PNBP) di Balai Riset Perikanan Perairan Umum dan Penyuluhan Perikanan (BRPPUPP) Pajak yang ditinjau dari sisi keakuratan pencatatan, kepatuhan pengelolaan, serta tingkat keefektifan. kemudian dianalisis dengan menggunakan Metode analisis deskriptif kualitatif. Hasil penelitian ini menjukan bahwa persentase PNBP untuk di Balai Riset Perikanan Perairan Umum dan Penyuluhan Perikanan di tahun 2019 realisasi penerimaan PNBP tidak mencapai target yang menunjukan bahwa kinerja pencapaian target sebesar 89.5%, Sedangkan jumlah penerimaan pada tahun 2020 menggambarkan keefektifan kebijakan PNBP melebihi target sebesar 198.9%. Kata kunci: PNBP,BRPPUPP